Cephalic salivary gland ultrastructure of worker and queen eusocial bees (Hymenoptera, Apidae) - Poiani, Silvana Beani [UNESP]; da Cruz-Landim, Carminda [UNESP] (Brill Academic Publishers, 2009)
Eusocial bees present a pair of functional salivary glands in head, the cephalic salivary glands. These glands from workers and queens of two eusocial bee species, Apis mellifera and Scaptotrigona postica, were examined at different life stages using routine transmission electron microscopy techniques to correlate morphology and gland functions. Ultrastructural features of worker and queen glands ducts and secretory units were descriptively compared between species. The duct cells present basal plasma membrane invaginations reaching the apical region. Intercellular space and invaginations contain material of similar electron-density to the basal lamina, suggesting that substances might be directly absorbed from the hemolymph to the gland lumen. The secretory cells are rich in smooth endoplasmic reticulum, mitochondria, Golgi, and vesicles typical of lipid secretion. Secretory cells in S. postica become flattened with age in contrast to A. mellifera, where cells remained cuboidal. Mitochondria are associated with secretory vesicles and may become lipid deposits. A possible role of worker and queen secretion is discussed, taking changes in caste gland morphology and their function in the colony into account. (C) Koninklijke Brill NV. Leiden, 2009
Keywords: Apis mellifera; labial gland; lipid; mitochondria; pheromone; Scaptotrigona postica